(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The potential of the new field of behavioral finance is enormous. Policymakers, institutions,market infrastructure institutions, and businesses all have a hard time making sense of individualinvestors’ behavior in the stock market because there isn’t enough literature in the Indian context.Responses to various stimuli or characteristics are the root of the observed behavior. In this studydetermining saving instrument and investment opportunities factors.